2021
DOI: 10.1002/mmce.23035
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency hybrid continuous mode power amplifier with input and output harmonic engineering

Abstract: This paper intensely studies the impact of the input nonlinearity caused by the transistor's feedback on the hybrid continuous class‐F power amplifier. The research extends the influence of input harmonics on class‐F power amplifiers to a more general form. Through waveform engineering, the impact of feedback is analyzed. By analyzing the change in cutoff angle caused by input nonlinearity, the change of the drain voltage and current waveforms of the hybrid continuous class‐F power amplifier can be obtained. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…It can be observed that the PA proposed here has the largest average efficiency, although the bandwidth of PAs in several works is wider than that presented in this work. Moreover, compared this work to those works [24][25][26][27] with similar frequency bands, it is clearer that the PA designed in this work is competitive in term of the average efficiency, which demonstrates that the expansion of the operating bandwidth in this paper does not come at the expense of efficiency.…”
Section: Experiments and Discussionmentioning
confidence: 64%
“…It can be observed that the PA proposed here has the largest average efficiency, although the bandwidth of PAs in several works is wider than that presented in this work. Moreover, compared this work to those works [24][25][26][27] with similar frequency bands, it is clearer that the PA designed in this work is competitive in term of the average efficiency, which demonstrates that the expansion of the operating bandwidth in this paper does not come at the expense of efficiency.…”
Section: Experiments and Discussionmentioning
confidence: 64%